Wicca - Bostulim, Regina Célia (2007)
The work is an study of Wicca neopagan religion which appeared in the 50s. Inside this study, Wicca and the figure of the witch are analyzed, in special their manifestations into the mass media, which influences Brazilian children and teens. It also analyses how Wicca occurs as an educative post modern phenomena, through Internet, into the pc game Runescape. The history of Wicca and the Inquisition are also analyzed, and their connections with the figure of the Great Mother and feminism.